ChemInform Abstract: Progress in the Development of Pyrophosphate Bioisosteres: Synthesis and Biomedical Potential of 1‐Fluoro‐ and 1, 1‐Difluoromethylene‐1, 1‐bisphosphonates. Issue 46 (18th November 2014) - Romanenko, Vadim D.; Kukhar, Valery P.
Abstract Review: 93 refs.